THE UNIQUENESS OF HUMAN EXISTENCE IN MODERN SOCIAL COMMUNICATIONS - Drotianko, Liubov (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2024)
Introduction. The existence of a large number of social interactions on a global scale causes the creation of various manipulative technologies of influence on the consciousness and psyche of people. Therefore, an urgent problem for philosophers and scientists is to identify the peculiarities of this influence and to find ways to preserve the uniqueness of the individual's existence. The aim of the study is to identify the specifics of the impact of social communications on individual consciousness and psyche, especially in computer social networks, and to outline possible ways to preserve the uniqueness and originality of a person's individual being in the processes of social communication. Research methods The main methodological tools were philosophical and anthropological, hermeneutical and socio-cultural research approaches in their dialectical interaction. Research results. It is substantiated that the fundamental characteristic of a person is his or her sociality, which is formed in the process of socialisation and social communications. It ensures the ability to make a personal choice of the self-being and preserve individual uniqueness. The most important means of this is a thorough modern education, which can be obtained in schools and other educational institutions, as they develop critical thinking skills. And the state must ensure the preservation of the mental health of children and adolescents by adopting appropriate laws in the field of social information and communication networks. Discussion. It is noted that the problem of the impact of social communications on human existence is widely discussed in the scientific and philosophical discourses of our time. The author presents the points of view of such researchers as M. Castells, O. P. Antipova, O. S. Polishchuk, O. V. Polishchuk and others. Conclusions. It is shown that the self-preservation of the uniqueness of human existence is ensured by the presence of human spirituality, which is laid down from childhood, in the process of acquiring knowledge, assimilating social values, etc. The problem of building and self-preservation of the uniqueness of human existence arises in modern society in the system of social communications as a cornerstone for the entire Ukrainian (and not only) society.